Intraorganisational Knowledge Transfer in Security-Critical Environments: A Conceptual Framework for High Reliability Organisations - Müller, Johannes C.; Kern, Eva-Maria; Holling, Jana M. (European journal for security research, 2021)
The purpose of this paper is to discuss the central role of knowledge transfer for high reliability organisations (HROs) and to present new empirically based findings in this context. An explorative approach is used to investigate how HROs deal with the transfer of operational knowledge. Twenty-eight expert interviews with members of five different HROs were conducted and analysed by means of a qualitative data analysis. The conceptual framework presents intraorganisational knowledge transfer in a cyclical way, defining operational knowledge as particularly relevant for HROs. Four influencing factors are highlighted in this context. Informal forms of knowledge transfer turn out to be particularly relevant for HROs, despite their hierarchical structures. Although previous contributions investigate the management of knowledge and its transfer in a broad sense, this paper specifically addresses HROs as a research subject, analysing the transfer of operationally relevant knowledge in several HROs on an empirically substantiated basis.